2020
DOI: 10.24996/ijs.2020.61.3.4
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Association Between IL-17 and HOMA-IR in Iraqi Type 2 Diabetic Patients

Abstract: Type 2 Diabetes Mellitus (T2DM) is the furthermost common form of DM which is identified by hyperglycemia, insulin resistance, and relative insulin deficiency. This study aims to detect the role of interleukin-17 (IL-17) in patients with T2DM compared with the healthy control and to investigate the relationship between IL-17 and insulin resistance. The study involved 50 Iraqi T2DM patients, randomly selected with an age range of 33-71 years .For the purpose of comparison, 30 Iraqi healthy persons with an age r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Insulin resistance factors, HOMA-IR, HbA1C, and FBG were all significantly increased and showed positive correlation with UII increase, while QUICKI-IS showed a high significant but negative correlation with UII (r= -0.528 p= 0.0001). These results suggest UII tendencies to impair Bcell functions through fluctuations and disturbances of insulin regulation via the six pathways that were mentioned earlier in our discussion [43,44]. Interestingly, UII showed a synergistically significant increase with the increase in ET-I levels, which is another potent vasoconstrictor that has a major role in diabetic complications.…”
Section: Discussionsupporting
confidence: 68%
“…Insulin resistance factors, HOMA-IR, HbA1C, and FBG were all significantly increased and showed positive correlation with UII increase, while QUICKI-IS showed a high significant but negative correlation with UII (r= -0.528 p= 0.0001). These results suggest UII tendencies to impair Bcell functions through fluctuations and disturbances of insulin regulation via the six pathways that were mentioned earlier in our discussion [43,44]. Interestingly, UII showed a synergistically significant increase with the increase in ET-I levels, which is another potent vasoconstrictor that has a major role in diabetic complications.…”
Section: Discussionsupporting
confidence: 68%
“…In fact, many chronic inflammatory disorders such as rheumatoid arthritis, psoriasis, and MS are associated with high IL-17A levels but, according to the current best knowledge, variations in IL-17 were not previously reported, which could be important for the various phases of the disease and its heterogeneity [26]. Another study that detected the relationship between IL-17 and insulin resistance found a crucial role of IL-17 in autoimmune disease [27].…”
Section: Interleukin-17amentioning
confidence: 95%
“…The results of the measurement of serum interleukin-17 levels showed significantly higher levels (P≤0.001) in pregnant women (468.38±50.62 Pg/ml) as compares to non-pregnant ones (144.39±3.98 Pg/ml), as shown in Table -2 Studies previously explained that serum IL-17 levels increase significantly in pregnant women at the third trimester in comparison with the beginning of the first trimester. The mean level of 17 increased up with the period of pregnancy to the last trimester [20,21,22]. Another study revealed no significant differences in the proportion of IL-17 cells among pregnant and non-pregnant women [23].…”
Section: Resultsmentioning
confidence: 93%